Manufacturing method of LCP extrusion film
Patent Information
- Application Number
- JP2020204359
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-12-09
AI Technical Summary
【0017】 本発明の一態様によれば、フィルム表面のみならずフィルム内部においても熱可塑性液晶ポリマーの分子配向や内部歪み等が緩和されたLCP押出フィルムを再現性よく且つ簡易に得ることのできる新規な製造方法等を提供することができる。
Smart Images

Figure 0007638689000005 
Figure 0007638689000006 
Figure 0007638689000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an extruded LCP film. [Background technology]
[0002] Conventionally, as an insulating material for circuit boards, a varnish-impregnated composite material is known, which is obtained by impregnating a glass cloth with a varnish containing a thermosetting resin such as an epoxy resin, an inorganic filler, a solvent, etc., and then hot press molding the glass cloth. However, this manufacturing method has poor process tolerance during manufacturing, and is inferior in productivity, from the viewpoint of, for example, the resin flow during varnish impregnation and the hardening property during hot press molding. In addition, thermosetting resins are prone to absorbing moisture, and the dimensions change with the moisture absorption, so the dimensional accuracy (heated dimensional accuracy) of the obtained varnish-impregnated composite material is inferior.
[0003] On the other hand, liquid crystal polymers (LCPs) are polymers that exhibit liquid crystallinity in a molten state or in a solution state. In particular, thermotropic liquid crystal polymers that exhibit liquid crystallinity in a molten state can be extrusion molded, and have excellent properties such as high gas barrier properties, high film strength, high heat resistance, high insulation, low water absorption, and low dielectric properties in the high frequency range. For this reason, films using thermoplastic liquid crystal polymers are being considered for practical use in gas barrier film material applications, electronic material applications, and electrical insulating material applications.
[0004] However, when actually performing single-layer extrusion molding, it was found that due to the high degree of liquid crystal orientation possessed by thermoplastic liquid crystal polymers, it was difficult to obtain a thermoplastic liquid crystal polymer film that has high industrial value, i.e., a thermoplastic liquid crystal polymer film that has excellent thickness accuracy and good appearance and surface flatness.
[0005] Therefore, for example, Patent Document 1 discloses that a three-layer coextrusion die is used instead of a single-layer extrusion die, and a wholly aromatic polyester-based thermotropic liquid crystal polymer is co-extruded as an intermediate layer with a polyolefin resin or polycarbonate resin as both outer layers to form a three-layer laminate film in which the intermediate layer is a thermoplastic liquid crystal polymer layer and both outer layers are thermoplastic resin layers, and the thermoplastic resin layers of both outer layers are peeled off to remove the intermediate layer as a film, thereby obtaining a thermoplastic liquid crystal polymer film with excellent thickness accuracy and good appearance and surface flatness.
[0006] Furthermore, for example, Patent Document 2 discloses that the strength in the TD (Transverse Direction) direction relative to the MD (Machine Direction) direction in the thermoplastic liquid crystal polymer film described in Patent Document 1 is not practically sufficient, and that by using a feedblock type three-layer coextrusion die instead of a multi-manifold type coextrusion die, the anisotropy of the strength in the TD and MD (Machine Direction) directions of the resulting thermoplastic liquid crystal polymer film is alleviated. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 63-31729 [Patent Document 2] Japanese Patent Application Publication No. 2-178016 Summary of the Invention [Problem to be solved by the invention]
[0008] Insulating materials for circuit boards using liquid crystal polymers have been attracting attention in recent years as insulating materials for circuit boards such as flexible printed circuit boards (FPCs), flexible printed circuit board laminates, and fiber-reinforced flexible laminates in the upcoming 5th generation mobile communication systems (5G) and millimeter wave radar, due to their excellent high-frequency characteristics and low dielectric properties.
[0009] The techniques described in the above Patent Documents 1 and 2 are said to be capable of realizing a thermoplastic liquid crystal polymer film having excellent thickness accuracy and good appearance and surface flatness. However, in reality, although peeling of the skin layer and peeling of fibrillated fibers caused by the thermoplastic liquid crystal polymer being highly molecular oriented on the film surface can be suppressed, the thermoplastic liquid crystal polymer films described in Patent Documents 1 and 2 still have a high molecular orientation of the thermoplastic liquid crystal polymer as a whole film, and are not practically usable as an insulating material for circuit boards.
[0010] The present invention has been made in view of the above problems. An object of the present invention is to provide a novel production method and the like that can easily and reproducibly obtain an LCP extruded film in which the molecular orientation and internal strain of the thermoplastic liquid crystal polymer are relaxed not only on the film surface but also inside the film. [Means for solving the problem]
[0011] As a result of intensive research aimed at solving the above problems, the inventors have discovered a new manufacturing method that can easily and reproducibly obtain an LCP extruded film in which the molecular orientation and internal distortion of the thermoplastic liquid crystal polymer are alleviated not only on the film surface but also inside the film, and have completed the present invention.
[0012] That is, the present invention provides various specific embodiments as shown below. (1) A step of preparing a resin composition A for a first surface layer containing a thermoplastic resin, a resin composition B for a central layer containing a thermoplastic liquid crystal polymer, and a resin composition C for a second surface layer containing a thermoplastic resin, respectively; a step of co-extruding the resin composition A, the resin composition B, and the resin composition C from a two-kind three-layer extruder under conditions of a shear stress of 40 kPa or less and a drawdown ratio of 3.5 or less to form a two-kind three-layer film having at least the first surface layer, the central layer, and the second surface layer in this order; and a step of removing the first and second surface layers from the two-kind three-layer film to form an LCP extruded film having a thickness of 15 μm to 300 μm, wherein the orientation degree α1 (%) including the exposed film surface S1 and the orientation degree α2 (%) including the film surface S2 located at a depth of 5 μm from the film surface S1, which is exposed by etching the film surface S1 in the thickness direction, satisfy the relationship of -4.0≦[(α2-α1) / α1]×100≦0.0, and The method for producing an extruded LCP film includes obtaining the extruded LCP film having a linear expansion coefficient in the MD direction and the TD direction at 23 to 200° C. within the range of −30 to 55 ppm / K as measured by a TMA method in accordance with K7197.
[0013] (2) The method for producing an extruded LCP film according to (1), wherein the thermoplastic liquid crystal polymer contains a (wholly) aromatic polyester resin.
[0014] (3) The method for producing an LCP extruded film according to (1) or (2), wherein the thermoplastic resin comprises one selected from the group consisting of polyolefin resins, acrylic resins, polyamide resins, acrylonitrile-butadiene-styrene copolymers, polystyrene, polyvinyl chloride, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, polyether ether ketone, and polyphenyl sulfide.
[0015] (4) The method for producing an extruded LCP film according to any one of (1) to (3), wherein the resin composition B further contains an inorganic filler. (5) The method for producing an extruded LCP film according to any one of (1) to (4), wherein the resin composition A, the resin composition B, and the resin composition C are co-extruded from a T-die. (6) The method for producing an extruded LCP film according to any one of (1) to (5), which produces the extruded LCP film having a linear expansion coefficient of 55 ppm / K or less in the TD direction.
[0016] (7) The method for producing an extruded LCP film according to any one of (1) to (6), further comprising heating and pressurizing the extruded LCP film obtained under conditions of 200 to 360°C. (8) The method for producing an extruded LCP film according to any one of (1) to (7), wherein the extruded LCP film does not have a skin layer on the film surface S1 that is tape-peelable in an adhesion test by a cross-cut method in accordance with JIS K5600-5-6. Effect of the Invention
[0017] According to one aspect of the present invention, a novel manufacturing method can be provided that can easily and reproducibly obtain an LCP extruded film in which the molecular orientation and internal strain of the thermoplastic liquid crystal polymer are relaxed not only on the film surface but also inside the film. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an embodiment of an LCP extruded film. [Diagram 2] FIG. 2 is a conceptual diagram showing the principle of calculating the degree of orientation based on the area ratio of the orientation peak. [Diagram 3] FIG. 1 illustrates a co-extrusion process for an LCP extruded film according to one embodiment. [Figure 4] FIG. 1 illustrates a co-extrusion process for an LCP extruded film according to one embodiment. [Diagram 5] FIG. 1 illustrates a co-extrusion process for an LCP extruded film according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. The positional relationships such as up, down, left and right are based on the positional relationships shown in the drawings unless otherwise specified. The dimensional ratios of the drawings are not limited to the ratios shown. However, the following embodiments are examples for explaining the present invention, and the present invention is not limited to these. That is, the present invention can be practiced with any changes within the scope of the gist of the present invention. In this specification, for example, the expression of a numerical range such as "1 to 100" includes both the lower limit "1" and the upper limit "100". The same applies to the expression of other numerical ranges.
[0020] (LCP extrusion film) 1 is a schematic cross-sectional view showing a main portion of an extruded LCP film 100 of this embodiment. The extruded LCP film 100 of this embodiment is formed by extruding a thermoplastic liquid crystal polymer into a film having a thickness of 15 μm or more and 300 μm or less.
[0021] As mentioned above, in the conventional LCP extrusion film, the thermoplastic liquid crystal polymer was highly molecular oriented on the film surface (film surface S1), such as peeling of the skin layer or peeling of the fibrillated fibers. This is presumably because the thermoplastic liquid crystal polymer was highly oriented on the surface of the extrusion molded body due to shear stress from the side of the device during extrusion. It was confirmed that the extreme molecular orientation of the thermoplastic liquid crystal polymer on the film surface was alleviated by the improvements in Patent Documents 1 and 2, but at the same time, the present inventors found that it was not possible to realize a material that could withstand the required performance as an insulating material for circuit boards by only controlling the molecular orientation of the thermoplastic liquid crystal polymer on the film surface.
[0022] Unlike the conventional technology, the LCP extrusion film 100 of this embodiment is characterized in that the molecular orientation and internal strain of the thermoplastic liquid crystal polymer are relaxed not only on the film surface (film surface S1) but also inside the film (film surface S2). That is, the LCP extrusion film 100 of this embodiment is characterized in that the orientation degree α1 (%) including the exposed film surface S1 and the orientation degree α2 (%) including the film surface S2 located at a depth of 5 μm from the film surface S1, which is exposed by etching the film surface S1 in the thickness direction, satisfy the relationship of -4.0≦[(α2-α1) / α1]×100≦0.0, and the linear expansion coefficient in the MD direction and the TD direction at 23 to 200° C. measured by the TMA method according to JIS K7197 is within the range of -30 to 55 ppm / K. Further details will be described below.
[0023] As the LCP extruded film 100, an extruded film such as a T-die extruded film is preferably used. As the LCP extruded film 100, a thermoplastic liquid crystal polymer layer that is an intermediate layer (core layer) of a three-layer coextruded film having a laminated structure in which a thermoplastic resin layer, a thermoplastic liquid crystal polymer layer, and a thermoplastic resin layer are arranged at least in this order is also preferably used. In this case, by removing the thermoplastic resin layers of both outer layers of the three-layer coextruded film, it can be used as a single-layer thermoplastic liquid crystal polymer film (LCP extruded film 100). Compared to woven fabrics or nonwoven fabrics made of thermoplastic liquid crystal polymer fibers, extruded films of thermoplastic liquid crystal polymers can be produced at low cost and with uniform quality.
[0024] The thermoplastic liquid crystal polymer contained in the LCP extruded film 100 may be any known one in the art, and the type is not particularly limited. The liquid crystal polymer is a polymer that forms an optically anisotropic molten phase, and a representative example is a thermotropic liquid crystal compound. The properties of the anisotropic molten phase can be confirmed by a known method, such as a polarized light inspection method using crossed polarizers. More specifically, the anisotropic molten phase can be confirmed by observing a sample placed on a Leitz hot stage at a magnification of 40 times under a nitrogen atmosphere using a Leitz polarizing microscope.
[0025] Specific examples of thermoplastic liquid crystal polymers include, but are not limited to, those obtained by polycondensation of monomers such as aromatic or aliphatic dihydroxy compounds, aromatic or aliphatic dicarboxylic acids, aromatic hydroxycarboxylic acids, aromatic diamines, aromatic hydroxyamines, and aromatic aminocarboxylic acids. The thermoplastic liquid crystal polymer is preferably a copolymer. Specific examples include, but are not limited to, aromatic polyamide resins obtained by polycondensation of monomers such as aromatic hydroxycarboxylic acids, aromatic diamines, and aromatic hydroxyamines; (all) aromatic polyester resins obtained by polycondensation of monomers such as aromatic diols, aromatic carboxylic acids, and aromatic hydroxycarboxylic acids; and the like. These can be used alone or in any combination and ratio of two or more.
[0026] Thermoplastic liquid crystal polymers are generally classified into I type, II type, III type, etc., from the viewpoint of heat distortion temperature (TDUL). Any type of thermoplastic liquid crystal polymer can be suitably used for the LCP extruded film 100 of the present embodiment, and may be appropriately selected depending on the application. For example, in electronic circuit board applications requiring application to lead-free solder at about 230 to 260°C, a highly heat-resistant I type thermoplastic liquid crystal polymer with a TDUL of about 250 to 350°C and a relatively heat-resistant II type thermoplastic liquid crystal polymer with a TDUL of about 240 to 250°C are suitably used.
[0027] Among these, (fully) aromatic polyester resins that exhibit thermotropic liquid crystal-like properties and have a melting point of 250°C or more, preferably 280°C to 380°C, are preferably used. As such (fully) aromatic polyester resins, for example, (fully) aromatic polyester resins that are synthesized from monomers such as aromatic diols, aromatic carboxylic acids, and hydroxycarboxylic acids and exhibit liquid crystallinity when melted are known. Representative examples include polycondensates of ethylene terephthalate and parahydroxybenzoic acid, polycondensates of phenol and phthalic acid and parahydroxybenzoic acid, and polycondensates of 2,6-hydroxynaphthoic acid and parahydroxybenzoic acid, but are not particularly limited thereto. The (fully) aromatic polyester resins can be used alone or in any combination and ratio of two or more. Depending on the required performance, a wholly aromatic polyester resin having a relatively high melting point or high heat distortion temperature and high heat resistance, or an aromatic polyester resin having a relatively low melting point or low heat distortion temperature and excellent moldability can be used.
[0028] A preferred embodiment is a (fully) aromatic polyester resin having a basic structure of 6-hydroxy-2-naphthoic acid and its derivatives (hereinafter, sometimes simply referred to as "monomer component A") and at least one monomer component selected from the group consisting of parahydroxybenzoic acid, terephthalic acid, isophthalic acid, 6-naphthalenedicarboxylic acid, 4,4'-biphenol, bisphenol A, hydroquinone, 4,4-dihydroxybiphenol, ethylene terephthalate, and derivatives thereof (hereinafter, sometimes simply referred to as "monomer component B"). In a molten state, such a (fully) aromatic polyester resin forms an anisotropic molten phase in which linear chains of molecules are regularly arranged, typically exhibiting thermotropic liquid crystal-like properties, and has excellent basic performance in terms of mechanical properties, electrical properties, high frequency properties, heat resistance, moisture absorption, and the like.
[0029] In addition, the (all) aromatic polyester resin of the above-mentioned preferred embodiment can have any structure as long as it has the monomer component A and the monomer component B as essential units. For example, it may have two or more kinds of the monomer component A, or it may have three or more kinds of the monomer component A. In addition, the (all) aromatic polyester resin of the above-mentioned preferred embodiment may contain another monomer component (hereinafter, simply referred to as "monomer component C") other than the monomer component A and the monomer component B. That is, the (all) aromatic polyester resin of the above-mentioned preferred embodiment may be a two-component or more polycondensate consisting of only the monomer component A and the monomer component B, or a three-component or more polycondensate consisting of the monomer component A, the monomer component B, and the monomer component C. Examples of the other monomer components include those other than the above-mentioned monomer component A and the monomer component B, specifically, aromatic or aliphatic dihydroxy compounds and derivatives thereof; aromatic or aliphatic dicarboxylic acids and derivatives thereof; aromatic hydroxycarboxylic acids and derivatives thereof; aromatic diamines, aromatic hydroxyamines, or aromatic aminocarboxylic acids and derivatives thereof; and the like, but are not particularly limited thereto. The other monomer components may be used either alone or in any combination and ratio of two or more kinds.
[0030] In this specification, the term "derivative" refers to a monomer component having a modification group such as a halogen atom (e.g., fluorine atom, chlorine atom, bromine atom, iodine atom), an alkyl group having 1 to 5 carbon atoms (e.g., methyl group, ethyl group, n-propyl group, isopropyl group, n-butyl group, isobutyl group, s-butyl group, t-butyl group, etc.), an aryl group such as a phenyl group, a hydroxyl group, an alkoxy group having 1 to 5 carbon atoms (e.g., methoxy group, ethoxy group, etc.), a carbonyl group, -O-, -S-, -CH2-, etc., introduced therein (hereinafter, this may be referred to as a "monomer component having a substituent"). Here, the "derivative" may be an ester-forming monomer such as an acylation product, an ester derivative, or an acid halide of the monomer components A and B which may have the above-mentioned modification group.
[0031] Particularly preferred embodiments include binary polycondensates of parahydroxybenzoic acid and its derivatives with 6-hydroxy-2-naphthoic acid and its derivatives; ternary or higher polycondensates of parahydroxybenzoic acid and its derivatives, 6-hydroxy-2-naphthoic acid and its derivatives, and monomer component C; and polycondensates of parahydroxybenzoic acid and its derivatives, 6-hydroxy-2-naphthoic acid and its derivatives, and terephthalic acid, isophthalic acid, 6-naphthalenedicarboxylic acid, 4,4'-biphenol, bisphenol A, hydroquinone, 4,4-dihydroxybiphenol. and ternary or higher polycondensates consisting of parahydroxybenzoic acid and its derivatives, 6-hydroxy-2-naphthoic acid and its derivatives, terephthalic acid, isophthalic acid, 6-naphthalenedicarboxylic acid, 4,4'-biphenol, bisphenol A, hydroquinone, 4,4-dihydroxybiphenol, ethylene terephthalate, and their derivatives, and one or more monomer components C. These can be obtained as having a relatively low melting point compared to, for example, homopolymers of parahydroxybenzoic acid, and therefore, thermoplastic liquid crystal polymers using these have excellent moldability when thermocompressed to an adherend.
[0032] From the viewpoint of lowering the melting point of the (all) aromatic polyester resin, improving the moldability during thermocompression bonding of the LCP extruded film 100 to an adherend, or obtaining high peel strength when the LCP extruded film 100 is thermocompression bonded to a metal foil, the molar ratio of the monomer component A to the (all) aromatic polyester resin is preferably 10 mol% or more and 90 mol% or less, more preferably 30 mol% or more and 85 mol% or less, and even more preferably 50 mol% or more and 80 mol% or less. Similarly, the molar ratio of the monomer component B to the (all) aromatic polyester resin is preferably 10 mol% or more and 90 mol% or less, more preferably 15 mol% or more and 70 mol% or less, and even more preferably 20 mol% or more and 50 mol% or less. In addition, the content of the monomer component C that may be contained in the (all) aromatic polyester resin is preferably 10 mol% or less, more preferably 8 mol% or less, even more preferably 5 mol% or less, and particularly preferably 3 mol% or less, in terms of molar ratio.
[0033] The (all) aromatic polyester resin can be synthesized by any known method, and is not particularly limited. Any known polycondensation method that forms an ester bond with the above-mentioned monomer components, such as melt polymerization, melt acidolysis, and slurry polymerization, can be used. When applying these polymerization methods, an acylation or acetylation step may be performed according to a conventional method.
[0034] The LCP extruded film 100 may further contain an inorganic filler. By containing an inorganic filler, it is possible to realize an LCP extruded film 100 with a reduced linear expansion coefficient, specifically, it is easy to obtain an LCP extruded film 100 with reduced anisotropy of the linear expansion coefficient in the MD direction, TD direction, and ZD direction (Z-axis direction; film thickness direction). Such an LCP extruded film 100 is particularly useful in rigid substrate applications requiring multi-layer lamination, for example.
[0035] The inorganic filler may be any of those known in the art, and the type is not particularly limited. For example, kaolin, calcined kaolin, calcined clay, uncalcined clay, silica (e.g., natural silica, fused silica, amorphous silica, hollow silica, wet silica, synthetic silica, aerosil, etc.), aluminum compounds (e.g., boehmite, aluminum hydroxide, alumina, hydrotalcite, aluminum borate, aluminum nitride, etc.), magnesium compounds (e.g., magnesium aluminometasilicate, magnesium carbonate, magnesium oxide, magnesium hydroxide, etc.), calcium compounds (e.g., calcium carbonate, Examples of the stannate include, but are not limited to, titanium oxide, zinc oxide, zirconium oxide, barium sulfate, zinc borate, barium metaborate, sodium borate, boron nitride, aggregated boron nitride, silicon nitride, carbon nitride, strontium titanate, barium titanate, and zinc stannate. These may be used alone or in combination of two or more. Among these, silica is preferred from the viewpoint of dielectric properties and the like.
[0036] The inorganic filler used here may be surface-treated as known in the art. The surface treatment can improve moisture resistance, adhesive strength, dispersibility, etc. Examples of surface treatment agents include, but are not limited to, silane coupling agents, titanate coupling agents, sulfonic acid esters, carboxylic acid esters, and phosphoric acid esters.
[0037] The median diameter (d50) of the inorganic filler can be appropriately set according to the required performance, and is not particularly limited. From the viewpoints of kneadability and handleability during preparation, the effect of reducing the linear expansion coefficient, etc., the d50 of the inorganic filler is preferably 0.01 μm to 50 μm, more preferably 0.03 μm to 50 μm, and even more preferably 0.1 μm to 50 μm. In this specification, the median diameter (d50) of the inorganic filler means a value measured on a volume basis by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-500 manufactured by Horiba, Ltd.).
[0038] The content of the inorganic filler is not particularly limited and can be appropriately set according to the required performance, taking into consideration the blending balance with other essential components and optional components. From the viewpoints of kneading and handling during preparation, the effect of reducing the linear expansion coefficient, etc., the content of the inorganic filler is preferably 1% by mass or more and 45% by mass or less in total, more preferably 3% by mass or more and 40% by mass or less in total, and even more preferably 5% by mass or more and 35% by mass or less in total, calculated as solid content relative to the total amount of the LCP extruded film 100.
[0039] The LCP extruded film 100 may contain resin components other than the above-mentioned thermoplastic liquid crystal polymer (hereinafter, may be simply referred to as "other resin components"), such as thermosetting resins and thermoplastic resins, within a range that does not excessively impair the effects of the present invention. In addition, the LCP extruded film 100 may contain additives known in the art, such as release improvers such as higher fatty acids having 10 to 25 carbon atoms, higher fatty acid esters, higher fatty acid amides, higher fatty acid metal salts, polysiloxanes, and fluororesins; colorants such as dyes and pigments; organic fillers; antioxidants; heat stabilizers; light stabilizers; ultraviolet absorbers; flame retardants; antistatic agents; surfactants; rust inhibitors; defoamers; fluorescent agents, and the like, within a range that does not excessively impair the effects of the present invention. Each of these additives may be used alone or in combination of two or more. These additives may be included in the molten resin composition prepared when molding the LCP extruded film 100. The contents of these resin components and additives are not particularly limited, but from the viewpoints of molding processability, thermal stability, etc., they are preferably each 0.01 to 10 mass % relative to the total amount of 100 LCP extruded film, more preferably 0.1 to 7 mass %, and even more preferably 0.5 to 5 mass %.
[0040] The thickness of the LCP extruded film 100 can be appropriately set according to requirements and is not particularly limited. In consideration of handleability and productivity during extrusion molding, the thickness is preferably 15 μm to 300 μm, more preferably 18 μm to 250 μm, and even more preferably 20 μm to 200 μm.
[0041] In addition, in the LCP extrusion film 100 of this embodiment, from the viewpoint of alleviating molecular orientation and internal distortion of the thermoplastic liquid crystal polymer not only on the film surface (film surface S1) but also inside the film (film surface S2), the orientation degree α1 including the film surface S1 and the orientation degree α2 including the film surface S2 are adjusted to satisfy the relationship shown below. Preferably, −4.0≦[(α2−α1) / α1]×100≦0.0. More preferably, −3.0≦[(α2−α1) / α1]×100≦0.0. More preferably, −2.0≦[(α2−α1) / α1]×100≦0.0.
[0042] Here, the film surface S1 is the outermost surface of the LCP extruded film 100 of this embodiment, and is the exposed surface exposed toward the outside. The orientation degree including the film surface S1 (orientation degree α1) is preferably 39.0% or less, more preferably 38.5% or less, and even more preferably 38.0% or less. On the other hand, the film surface S2 is a surface newly exposed by etching the film surface S1 of the LCP extruded film 100 of this embodiment in the thickness direction, and is represented by a dashed line in FIG. 1 as a virtual surface located at a depth of 5 μm from the film surface S1. The orientation degree including this film surface S2 (orientation degree α2) is preferably 37.7% or less, more preferably 37.5% or less, and even more preferably 37.3% or less. In addition, the depth at which the film surface S2 is located does not need to be strictly 5 μm from the film surface S1, taking into account dissolution errors during etching, etc., and may be 5.0 μm or more from the film surface S1. The etching conditions for preparing the film surface S2 are not particularly limited, but should conform to the conditions described in the examples below in order to ensure objectivity between the measurement data.
[0043] In this specification, the orientation degrees α1, α2 (%) including the film surfaces S1, S2 of the LCP extruded film 100 refer to values calculated from the following formula based on the area ratio of the orientation peak in the diffraction intensity distribution curve obtained by performing X-ray diffraction measurement by a transmission method using an X-ray diffraction device. In general, when the measurement target has a low orientation degree (%), a broad diffraction peak with a low peak intensity is observed in the X-ray diffraction measurement, so that a calculation method based on the half-width of the orientation peak cannot guarantee high measurement accuracy. Therefore, in this specification, the orientation degrees α1, α2 (%) including the film surfaces S1, S2 are calculated using a calculation method based on the area ratio of the orientation peak, rather than the half-width of the orientation peak. Specifically, as shown in FIG. 2 and Equation 1, the calculation method is based on the area proportion of the orientation peak, in which the peak intensity (orientation component) is measured by 2θ / θ scan, and the intensity in the azimuth direction from 0° to 360° is measured by β scan to obtain the intensity distribution in the azimuth direction (base intensity (isotropic component)). The orientation degree (%) is calculated as the percentage of the area occupied by the orientation component excluding the area of the base isotropic component to the total area (area of the orientation component + area of the isotropic component).
number
[0044] On the other hand, the LCP extrusion film 100 of the present embodiment has not only the molecular orientation of the thermoplastic liquid crystal polymer represented by the above-mentioned degree of orientation, but also the molecular orientation of the thermoplastic liquid crystal polymer represented by the linear expansion coefficient in the MD direction and the TD direction sufficiently reduced. As mentioned above, the LCP extrusion film described in Patent Documents 1 and 2 of the prior art is protected by the thermoplastic resin layers of both outer layers during three-layer coextrusion, and this seems to relax the anisotropy of the strength in the MD direction and the TD direction of the obtained thermoplastic liquid crystal polymer film. However, in reality, the LCP extrusion film described in Patent Documents 1 and 2 has a stable linear expansion coefficient in the MD direction of about -20 ppm / K, while the linear expansion coefficient in the TD direction exceeds 55 ppm, and sometimes reaches about 100 ppm / K. As is clear from this, it is easily understood that the molecular orientation of the thermoplastic liquid crystal polymer still remains large in the LCP extrusion film described in Patent Documents 1 and 2 of the prior art, or the internal strain remains large in the entire film. Therefore, the molecular orientation and internal strain of the thermoplastic liquid crystal polymer in the entire LCP extruded film 100 must be controlled by a combination of the degree of orientation including the film surface and the linear expansion coefficient described above.
[0045] The linear expansion coefficients (CTE, α2, 23-200°C) of the LCP extruded film 100 in the MD and TD directions are within the ranges of -30 to 55 ppm / K. The LCP extruded film 100 having a linear expansion coefficient within such range is in a state in which internal strain and the like are sufficiently reduced. From the viewpoint of improving adhesion to metal foil, the linear expansion coefficient (CTE, α2, 23-200°C) of the LCP extruded film 100 in the MD direction is preferably within the range of -30 to 10 ppm / K, more preferably within the range of -25 to 5 ppm / K, and even more preferably within the range of -20 to 0 ppm / K. Furthermore, the coefficient of linear expansion in the TD direction (CTE, α2, 23 to 200°C) of the LCP extruded film 100 of this embodiment is preferably in the range of 0 to 55 ppm / K, more preferably in the range of 0 to 50 ppm / K, and even more preferably in the range of 0 to 45 ppm / K, from the viewpoint of improving adhesion to metal foil, etc.
[0046] In this specification, the linear expansion coefficient is measured by a TMA method according to JIS K7197, and the average linear expansion coefficient means the average value of the linear expansion coefficients at 23 to 200°C measured by the same method. The linear expansion coefficient measured here means the value when the LCP extruded film 100 is heated (1st heating) at a heating rate of 5°C / min, cooled (1st cooling) to the measurement environment temperature (23°C), and then heated a second time (2nd heating) at a heating rate of 5°C / min in order to see the value after removing the thermal history. Other detailed measurement conditions are in accordance with the conditions described in the examples described later.
[0047] On the other hand, the dielectric properties of the LCP extruded film 100 of the present embodiment can be appropriately set according to the desired performance, and are not particularly limited. r (36GHz) is preferably 3.0 or more and 3.7 or less, more preferably 3.0 to 3.5. Similarly, the dielectric tangent tanδ(36GHz) is preferably 0.0010 or more and 0.0050 or less, more preferably 0.0010 or more and 0.0045 or less. In this specification, the relative dielectric constant ε rand the dielectric loss tangent tanδ are values at 36 GHz measured by a cavity resonator vibration method in accordance with JIS K6471. Other detailed measurement conditions are in accordance with the conditions described in the examples described later.
[0048] (LCP extrusion film manufacturing method) The LCP extruded film 100 of this embodiment can be obtained by extruding a resin composition containing the above-mentioned thermoplastic liquid crystal polymer and optional components such as inorganic fillers and other resin components as necessary to a predetermined thickness. The extrusion method can be any known method, and the type is not particularly limited. For example, the T-die method or the inflation method; for example, the multi-manifold coextrusion method or the feed block coextrusion method; for example, the multi-layer coextrusion method such as the two-layer coextrusion method or the three-layer coextrusion method; can be applied in any combination.
[0049] Among these, from the viewpoint of ease of control of the molecular orientation of the thermoplastic liquid crystal polymer on the film surface (film surface S1) and inside the film (film surface S2), a preferred embodiment is a method in which the above-mentioned resin composition is extruded from a T-die by an extrusion molding method using a T-die (hereinafter, sometimes simply referred to as "T-die extrusion method") to form a film, and then, as necessary, a cooling treatment, a pressure bonding treatment, a pressurized heating treatment, etc. are performed to obtain a predetermined LCP extrusion film 100. Specifically, a resin composition A for a first surface layer containing a thermoplastic resin, a resin composition B for a central layer containing a thermoplastic liquid crystal polymer, and a resin composition C for a second surface layer containing a thermoplastic resin are each prepared, and these are co-extruded from a co-extrusion die of an extruder to extrude a three-layered co-extrusion melt, and an LCP extrusion film 100 is formed as a thermoplastic liquid crystal polymer layer of an intermediate layer. According to such co-extrusion molding, the molecular orientation of the thermoplastic liquid crystal polymer in the thermoplastic liquid crystal polymer layer of the intermediate layer is relaxed by being protected by the thermoplastic resin layers of both outer layers. A preferred embodiment of the method for producing the extruded LCP film 100 of this embodiment will be described in detail below.
[0050] 3 to 5 are diagrams showing a preferred embodiment of the manufacturing method of the LCP extruded film 100 of the present embodiment described above. Here, the above-mentioned resin composition B containing the above-mentioned thermoplastic liquid crystal polymer and optional components such as inorganic filler and other resin components as necessary is melt-extruded into a film shape from a T-die of an extruder. At this time, resin compositions A and C containing a thermoplastic resin are co-extruded on both sides of the above-mentioned film-shaped melt extrusion product to produce a co-extruded melt (three-layer laminated film) of a predetermined thickness having a first outer layer (peeling layer) containing a thermoplastic resin, an intermediate layer (LCP layer) containing a thermoplastic liquid crystal polymer, and a second outer layer (peeling layer) containing a thermoplastic resin. This co-extruded melt is drawn out by a take-up roll and sent to a cooling roll and a pressure-bonding roll. Thereafter, the first outer layer and the second outer layer are peeled off from the intermediate layer, and the thermoplastic resin layers of both outer layers and the thermoplastic liquid crystal polymer layer of the intermediate layer (LCP extruded film 100) are wound up on a take-up roll, respectively.
[0051] The preparation of the resin composition B containing the thermoplastic liquid crystal polymer may be carried out according to a conventional method, and is not particularly limited. The above-mentioned components can be manufactured and processed by known methods such as kneading, melt kneading, granulation, extrusion molding, pressing or injection molding. When melt kneading, kneading devices such as commonly used single-screw or twin-screw extruders and various kneaders can be used. When supplying each component to these melt kneading devices, the liquid crystal polymer, other resin components, inorganic fillers, additives, etc. may be dry-blended in advance using a mixing device such as a tumbler or Henschel mixer. When melt kneading, the cylinder setting temperature of the kneading device may be appropriately set and is not particularly limited, but is generally preferably in the range of from the melting point of the liquid crystal polymer to 360 ° C., and more preferably from the melting point of the liquid crystal polymer + 10 ° C. to 360 ° C.
[0052] The resin compositions A and C containing a thermoplastic resin may be prepared according to a conventional method, and are not particularly limited. Examples of the thermoplastic resin include polyolefin resins such as polyethylene, polypropylene, polymethylpentene, and ethylene-α-olefin copolymers, acrylic resins such as PMMA, polyamide resins, acrylonitrile-butadiene-styrene copolymers (ABS resins), polystyrene (PS), polyvinyl chloride, polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polycarbonate (PC), polyether ether ketone (PEEK), and polyphenyl sulfide (PPS), but are not particularly limited thereto. When the resin is made into a coextrusion melt, it effectively functions as a release layer, whether it is a polar resin such as polycarbonate or a non-polar resin such as polymethylpentene. These thermoplastic resins may be blended with optional components such as other resin components and inorganic fillers that may be contained in the above-mentioned LCP extruded film 100. The resin composition A and the resin composition C may have the same resin composition or different resin compositions, and may contain the same thermoplastic resin or different thermoplastic resins. The resin compositions A and C containing thermoplastic resins can be manufactured and processed by known methods such as kneading, melt kneading, granulation, extrusion molding, pressing or injection molding. When melt kneading, kneading devices such as commonly used single-screw or twin-screw extruders and various kneaders can be used. When supplying each component to these melt kneading devices, the thermoplastic resin, other resin components, inorganic fillers, additives, etc. may be dry blended in advance using a mixing device such as a tumbler or Henschel mixer. When melt kneading, the cylinder setting temperature of the kneading device may be appropriately set below a temperature at which the thermoplastic resin does not deteriorate due to thermal decomposition, and is not particularly limited, but is generally preferably above the melting point of the thermoplastic resin, and more preferably above the melting point of the thermoplastic resin + 10 ° C.
[0053] The conditions for co-extrusion are not particularly limited and may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc. For example, the set temperature of the cylinder of the extruder is not particularly limited and may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., but is preferably 230 to 360°C, more preferably 280 to 350°C.
[0054] Similarly, the die width (mm) of the T-die may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally preferably 200 to 2000 mm, and more preferably 400 to 1500 mm.
[0055] Furthermore, for example, the lip opening (mm) of the T-die may also be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally preferably 0.1 to 3.0 (mm), and more preferably 0.2 to 2.0 (mm).
[0056] For example, the shear rate (sec -1 Similarly, the extrusion speed may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally 100 to 1500 (sec -1 ), and more preferably 150 to 1000 (sec -1 ).
[0057] In addition, the total discharge amount of the resin composition from the T-die (mm 3 Similarly, the extrusion speed may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally 500 to 15,000 (mm 3 / sec), and more preferably 1500 to 10000 (mm 3 / sec).
[0058] On the other hand, the melt viscosity (Pa·sec) of the thermoplastic liquid crystal polymer may also be appropriately set according to the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally preferably 10 to 300 (Pa·sec), more preferably 20 to 250 (Pa·sec). The melt viscosity (Pa·sec) of the thermoplastic liquid crystal polymer means a value measured in accordance with JIS K7199 using a Capilograph 1D (manufactured by Toyo Seiki Seisakusho Co., Ltd.) under the conditions of a cylinder length of 10.00 mm, a cylinder diameter of 1.00 mm, and a barrel diameter of 9.55 mm under the conditions during the production of the LCP extruded film 100 (die temperature and shear rate of the lip wall).
[0059] Similarly, the take-up speed (mm / sec) of the co-extruded film may be appropriately set depending on the type and composition of the resin composition used, the desired performance of the target extruded film, etc., and is not particularly limited, but is generally preferably 15 to 1000 (mm / sec), and more preferably 20 to 500 (mm / sec).
[0060] Here, from the viewpoint of reducing the molecular orientation of the thermoplastic liquid crystal polymer in the MD direction during coextrusion, it is desirable that the shear stress (kPa) during coextrusion is low. If the shear stress during coextrusion is large, the thermoplastic liquid crystal polymer is likely to be highly oriented in the MD direction and internal strain is likely to remain, while if the shear stress during coextrusion is small, the molecular orientation of the thermoplastic liquid crystal polymer is likely to be reduced both on the film surface (film surface S1) and inside the film (film surface S2) and internal strain is likely to remain. The shear stress (kPa) during coextrusion is determined by the shear rate (sec) of the lip wall. -1) and the melt viscosity (Pa·sec) of the thermoplastic liquid crystal polymer, and the shear rate is a value calculated based on the total discharge amount of the resin composition during co-extrusion, the die width, and the lip opening. Therefore, the shear stress during co-extrusion can be controlled by adjusting each of these values. Specifically, the shear stress during co-extrusion is preferably 40 kPa or less, more preferably 38 kPa or less, and even more preferably 36 kPa or less. The lower limit is not particularly limited, but is preferably 5 kPa or more, more preferably 10 kPa or more, in consideration of productivity, etc.
[0061] In addition, from the viewpoint of reducing the molecular orientation of the thermoplastic liquid crystal polymer in the MD direction during coextrusion, it is desirable that the drawdown ratio during coextrusion is low. If the drawdown ratio during coextrusion is large, the thermoplastic liquid crystal polymer is likely to be highly oriented in the MD direction and internal strain is likely to remain, and if the drawdown ratio during coextrusion is small, the molecular orientation of the thermoplastic liquid crystal polymer is likely to be reduced both on the film surface (film surface S1) and inside the film (film surface S2) and internal strain is likely to remain. The drawdown ratio is a value expressed by the take-up speed (mm / sec) / flow rate of the thermoplastic liquid crystal polymer (mm / sec), and the flow rate of the thermoplastic liquid crystal polymer is a value calculated based on the total discharge amount of the resin composition during coextrusion, the die width, and the lip opening. Therefore, the drawdown ratio during coextrusion can be controlled by adjusting each of these values. Specifically, the drawdown ratio during coextrusion is preferably 3.5 or less, more preferably 3.3 or less, and even more preferably 3.1 or less. The lower limit is not particularly limited, but is preferably 1.0 or more, more preferably 1.2 or more, taking into consideration productivity and the like.
[0062] The thickness of the resulting LCP extruded film 100 can be appropriately set according to requirements and is not particularly limited. In consideration of handleability and productivity during extrusion molding, the thickness is preferably 15 μm to 300 μm, more preferably 18 μm to 250 μm, and even more preferably 20 μm to 200 μm.
[0063] The melting point (melting temperature) of the obtained LCP extruded film 100 is not particularly limited, but from the viewpoint of the heat resistance and processability of the film, the melting point (melting temperature) is preferably 200 to 400° C., and from the viewpoint of improving the thermocompression bonding to metal foil in particular, the melting point (melting temperature) is preferably 250 to 360° C., more preferably 260 to 355° C., even more preferably 270 to 350° C., and particularly preferably 275 to 345° C. In this specification, the melting point of the LCP extruded film 100 means the melting peak temperature in differential scanning calorimetry (DSC) when the extruded film is heated (1st heating) at a temperature rise rate of 20° C. / min in the temperature range of 30 to 400° C. using DSC8500 (manufactured by PerkinElmer) to see the value after eliminating the thermal history, and then cooled (1st cooling) at a temperature drop rate of 50° C. / min, and then heated a second time (2nd heating) at a temperature rise rate of 20° C. / min. Other conditions should be in accordance with the measurement conditions described in the Examples section below.
[0064] The extrusion-molded LCP extrusion film 100 can be used as is, but if necessary, a pressurizing and heating process can be carried out to further reduce the molecular orientation of the thermoplastic liquid crystal polymer or further release the internal strain.
[0065] The heat and pressure treatment may be performed by a method known in the art, such as a contact heat treatment or a non-contact heat treatment, and the type is not particularly limited. For example, heat setting may be performed using known equipment such as a non-contact heater, an oven, a blowing device, a heat roll, a cooling roll, a heat press, or a double-belt heat press. At this time, if necessary, a release film or a porous film known in the art may be arranged on the surface of the LCP extruded film 100, and the heat treatment may be performed. In addition, when performing this heat treatment, from the viewpoint of controlling the orientation, a heat and pressure molding method is preferably used in which a release film or a porous film is arranged on the front and back of the LCP extruded film 100, and the film is thermocompressed while being sandwiched between a pair of endless belts of a double-belt press, and then the release film or the porous film is removed. The heat and pressure molding method may be performed by referring to, for example, JP-A-2010-221694. The processing temperature when the LCP extrusion film 100 using the above resin composition is thermocompressed between the pair of endless belts of a double belt press is preferably higher than the melting point of the liquid crystal polymer and lower than 70°C higher than the melting point, more preferably higher than +5°C higher than the melting point and lower than 60°C higher than the melting point, and even more preferably higher than +10°C higher than the melting point and lower than 50°C higher than the melting point. The thermocompression bonding conditions can be appropriately set according to the desired performance, and are not particularly limited, but are preferably performed under conditions of a surface pressure of 0.5 to 10 MPa and a heating temperature of 250 to 430°C, more preferably under conditions of a surface pressure of 0.6 to 8 MPa and a heating temperature of 260 to 400°C, and even more preferably under conditions of a surface pressure of 0.7 to 6 MPa and a heating temperature of 270 to 370°C. On the other hand, when a non-contact heater or oven is used, it is preferably performed under conditions of, for example, 200 to 320°C for 1 to 20 hours.
[0066] In the LCP extrusion film 100 of this embodiment, the molecular orientation and internal strain of the thermoplastic liquid crystal polymer are relaxed not only on the film surface (film surface S1) but also inside the film (film surface S2), so it can be used as a material for circuit boards such as electronic circuit boards and multilayer boards. In addition, the LCP extrusion film 100 of this embodiment has excellent dielectric properties in the high frequency range, is easy to manufacture, and has excellent productivity, making it a particularly useful material as an insulating material for flexible printed circuit boards (FPCs) in fifth-generation mobile communication systems (5G), millimeter-wave radar, and the like. EXAMPLES
[0067] The features of the present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited thereto. That is, the materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. In addition, the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limits in the embodiment of the present invention, and the preferred numerical range may be a range defined by a combination of the above-mentioned upper or lower limit and the values of the following examples or the values of the examples.
[0068] [Melt Viscosity] The melt viscosity [Pa·sec] of each LCP extruded film was measured under the following conditions. Measuring equipment: Capillograph 1D (manufactured by Toyo Seiki Co., Ltd.) Equipment used: Cylinder length 10.00mm, cylinder diameter 1.00mm, barrel diameter 9.55mm Measurement conditions: Temperature [℃] and shear rate [sec ] during extrusion of each LCP extrusion film -1 ]
[0069] [Orientation degree] Using an X-ray diffraction device Smartlab (manufactured by Rigaku Corporation), X-ray diffraction measurements were performed on each LCP extrusion film including film surface S1 or film surface S2 by the transmission method, and the degree of orientation was measured. Here, a Cu sealed tube was used as the X-ray source, and X-ray diffraction measurements (2θ / θ scan, β scan) were performed by the parallel beam optical system and the transmission method. First, it was confirmed that there was a peak top at 2θ=19.5° in the 2θ / θ scan. Next, the intensity distribution in the azimuth angle direction was obtained by measuring the intensity from 0° to 360° for the diffraction peak at 2θ=19.5 in the β scan. The degree of orientation was calculated from the above formula based on the area ratio of the orientation peak from the base intensity (isotropic component) and peak intensity (orientation component) of the obtained β profile. The film surface S2 of each LCP extrusion film was adjusted by immersing each LCP extrusion film in a 70% aqueous monoethylamine solution (manufactured by Daicel Corporation) for 168 hours in a 23°C, 50% RH environment, etching both surfaces of each LCP extrusion film to a depth of 5 μm, washing with running water for 5 minutes, washing with distilled water, drying at 80°C for 1 hour, and cooling in a 23°C, 50% RH environment for 24 hours.
[0070] [Linear expansion coefficient] The linear expansion coefficient of each LCP extruded film was measured by the TMA method in accordance with JIS K7197. Measuring equipment: TMA 4000SE (NETZSCH) Measurement method: Tensile mode Measurement conditions: Sample size 25mm x 4mm x thickness 50μm Chuck distance: 20mm Temperature range: 23~200℃ (2nd RUN) Heating rate: 5℃ / min Atmosphere: Nitrogen (flow rate 50ml / min) Test load: 5gf *The value from the 2nd run was used to see the value after eliminating the thermal history.
[0071] [Tape peeling test] The film surface S1 of each LCP extrusion film was subjected to an adhesion test by a cross-cut method according to JIS K5600-5-6 to confirm the presence or absence of a skin layer. At this time, a 24 mm wide × 50 mm long cellophane tape (registered trademark) manufactured by Nichiban Co., Ltd. was used, and when the tape was peeled off and there was no peeling in the grid, it was judged as "no skin layer", and when there was peeling, it was judged as "skin layer present". ○ No skin layer × Skin layer
[0072] (Examples 1 to 3) The central layer was a type II thermoplastic liquid crystal polymer (a copolymer with a monomer composition of 74 mol% p-hydroxybenzoic acid and 26 mol% 6-hydroxy-2-naphthoic acid, at a temperature of 300°C and a shear rate of 500 sec -1 A two-kind three-layer film with a 50μm central layer was molded by co-extrusion at 300°C using a two-kind three-layer extruder equipped with a T-die with a die width of 600mm and a lip opening of 0.2-1.0mm by a T-die casting method under the molding conditions shown in Table 1. The polycarbonate films of both surface layers were peeled off from the molded two-kind three-layer film on a winding line, and the LCP extruded films of Examples 1 to 3 with a melting point of 280°C and a thickness of 50μm were obtained.
[0073] Comparative Example 1 Type II thermoplastic liquid crystal polymer (a copolymer of 74 mol% p-hydroxybenzoic acid and 26 mol% 6-hydroxy-2-naphthoic acid, temperature 300°C and shear rate 500 sec -1 The liquid crystal polymer was extruded at 300°C by a T-die casting method from a single-layer extruder equipped with a T-die having a die width of 600 mm and a lip opening of 0.3 mm under the molding conditions shown in Table 1 using a melt viscosity of 80 Pa sec. to obtain an LCP extruded film of Comparative Example 1 having a melting point of 280°C and a thickness of 50 μm.
[0074] (Comparative Examples 2 to 4) Except for changing the molding conditions as shown in Table 1, the same method as in Example 1 was used to obtain extruded LCP films of Comparative Examples 2 to 4 having a melting point of 280° C. and a thickness of 50 μm.
[0075] [Table 1]
[0076] (Examples 4 to 6) Instead of type II thermoplastic liquid crystal polymer, type I thermoplastic liquid crystal polymer (a copolymer of 79 mol% p-hydroxybenzoic acid, 20 mol% 6-hydroxy-2-naphthoic acid, and 1 mol% terephthalic acid, at a temperature of 330°C and a shear rate of 500 sec -1 Extruded LCP films of Examples 4 to 6 having a melting point of 315°C and a thickness of 50 μm were obtained in the same manner as in Example 1, except that a resin having a melt viscosity of 70 Pa sec was used for the central layer and each resin was co-extruded at 330°C.
[0077] Comparative Example 5 Instead of type II thermoplastic liquid crystal polymer, type I thermoplastic liquid crystal polymer (a copolymer of 79 mol% p-hydroxybenzoic acid, 20 mol% 6-hydroxy-2-naphthoic acid, and 1 mol% terephthalic acid, at a temperature of 330°C and a shear rate of 500 sec -1 An LCP extruded film of Comparative Example 2 having a melting point of 315°C and a thickness of 50 µm was obtained in the same manner as in Comparative Example 1, except that a liquid crystal polymer having a melt viscosity of 70 Pa·sec was used and the liquid crystal polymer was extruded at 330°C.
[0078] (Comparative Examples 6 to 8) Except for changing the molding conditions as shown in Table 2, the same method as in Example 4 was used to obtain extruded LCP films of Comparative Examples 6 to 8 each having a melting point of 315° C. and a thickness of 50 μm.
[0079] [Table 2]
[0080] (Examples 7 to 9) Extruded LCP films of Examples 7 to 9 having a melting point of 280° C. and a thickness of 50 μm were obtained in the same manner as in Example 1, except that polymethylpentene PMP (TPX MX004 manufactured by Mitsui Chemicals, Inc.) was used for the surface layers on both sides instead of polycarbonate.
[0081] (Comparative Examples 9 to 11) Except for changing the molding conditions as shown in Table 3, the same method as in Example 7 was used to obtain extruded LCP films of Comparative Examples 9 to 11 each having a melting point of 280° C. and a thickness of 50 μm.
[0082] [Table 3] [Industrial Applicability]
[0083] The extruded LCP film of the present invention can be widely and effectively used in applications such as electronic circuit boards, multilayer boards, high heat dissipation boards, flexible printed wiring boards, antenna boards, optoelectronic hybrid boards, and IC packages. In particular, since it is suitable for ultrafine processing and has high reliability, it can be widely and effectively used as an insulating material such as flexible printed wiring boards (FPCs) in fifth-generation mobile communication systems (5G) and millimeter-wave radars, as well as metal foil-clad laminates. [Explanation of symbols]
[0084] 100···LCP extrusion film 100a··· surface 100b...plane S1 Film surface S2: Film surface at a depth of 5 μm
Claims
1. A step of preparing a resin composition A for a first surface layer containing a thermoplastic resin, a resin composition B for a central layer containing a thermoplastic liquid crystal polymer, and a resin composition C for a second surface layer containing a thermoplastic resin; A process of co-extruding the resin composition A, the resin composition B, and the resin composition C from a two-kind three-layer extruder under conditions of a shear stress of 40 kPa or less and a drawdown ratio of 3.5 or less to form a two-kind three-layer film having at least the first surface layer, the central layer, and the second surface layer in this order; and The first and second surface layers are removed from the two-kind three-layer film to obtain an extruded LCP film having a thickness of 15 μm or more and 300 μm or less, in which an orientation degree α1 (%) including the exposed film surface S1 and an orientation degree α2 (%) including a film surface S2 located at a depth of 5 μm from the film surface S1 and exposed by etching the film surface S1 in the thickness direction satisfy the relationship of -4.0≦[(α2-α1) / α1]×100≦0.0, and the linear expansion coefficient in the MD direction and the TD direction at 23 to 200° C. measured by the TMA method in accordance with JIS K7197 is within the range of -30 to 55 ppm / K. Method for producing LCP extruded film.
2. The thermoplastic liquid crystal polymer contains a (wholly) aromatic polyester resin. A method for producing the extruded LCP film of claim 1.
3. The thermoplastic resin includes one selected from the group consisting of polyolefin resins, acrylic resins, polyamide resins, acrylonitrile-butadiene-styrene copolymers, polystyrene, polyvinyl chloride, polybutylene terephthalate, polyethylene terephthalate, polycarbonate, polyether ether ketone, and polyphenyl sulfide. A method for producing the extruded LCP film according to claim 1 or 2.
4. The resin composition B further contains an inorganic filler. A method for producing an extruded LCP film according to any one of claims 1 to 3.
5. The resin composition A, the resin composition B, and the resin composition C are co-extruded from a T-die. A method for producing an extruded LCP film according to any one of claims 1 to 4.
6. To obtain the LCP extruded film having a linear expansion coefficient in the TD direction of 55 ppm / K or less. A method for producing an extruded LCP film according to any one of claims 1 to 5.
7. The obtained LCP extruded film is subjected to a heat and pressure treatment under conditions of 200 to 360° C. A method for producing an extruded LCP film according to any one of claims 1 to 6.
8. The LCP extrusion film is obtained by testing the film surface S1 for adhesion using a cross-cut method in accordance with JIS K5600-5-6, and does not have a skin layer that can be peeled off with tape. A method for producing an extruded LCP film according to any one of claims 1 to 7.
Citation Information
Patent Citations
Manufacture of liquid crystal film
JP1988031729A
Liquid crystalline polymer film and manufacture thereof
JP1990178016A
Production method for multilayer foam sheet
JP2003181904A
Polarization film, method for manufacturing polarization film, and polarization plate and liquid crystal using the same
JP2008052170A
Co-extruded ultrathin film
JP2015507551A